Evaluation of inter-batch variability in the establishing and quality control of glucose - Moya Salazar, J. J.; Pio Dávila, L. (UANL. Facultad de Medicina, 2016)
This research evaluated the inter-batch variability in the identification and quality control of glucose, according to international specifications detailed in the guide CLSI EP-15. Type of qualitative research, analytical, not experimental, prospective cross-sectional conducted at the Department of Clinical Laboratory at Polyclinic ‘‘La Fe’’ during January 2015 was performed. The inter-batch variability for glucose in the semi-automated biochemical analyzer URIT-810 with liquid enzyme glucose-LS reagent (GOD-PAP) Valtek® batch 140825 was evaluated. The calibrators (CS) were the lot CS-A: 140 428, CS-B: 120912 and CS-C: 131 202. Data analysis was performed in SPSS version 20.0 statistical analyzer and Microsoft Office Excel 2010 for Windows. The values found by calculating the sigma metric were: 2 (SE −0.35), 0 (SE 1.65) −0.9 (SE −0.75) to CS-A, CS-B and CS-C, respectively (p < 0.05). Only CS-A might be able to improve their performance, although with greater cost. Sub-optimal performance characteristics by using standard calibrators show high inter-lot variability, suggesting the choice and search for a new and better calibration method to ensure results that contain no medically important errors affecting patient health.